2017
DOI: 10.1073/pnas.1704882114
|View full text |Cite
|
Sign up to set email alerts
|

Individuals with greater science literacy and education have more polarized beliefs on controversial science topics

Abstract: Although Americans generally hold science in high regard and respect its findings, for some contested issues, such as the existence of anthropogenic climate change, public opinion is polarized along religious and political lines. We ask whether individuals with more general education and greater science knowledge, measured in terms of science education and science literacy, display more (or less) polarized beliefs on several such issues. We report secondary analyses of a nationally representative dataset (the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

36
378
6
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 407 publications
(426 citation statements)
references
References 42 publications
36
378
6
6
Order By: Relevance
“…Kahan et al (2012) show that polarization about climate change is greatest among individuals with the highest degrees of scientific literary and technical reasoning capacity. Drummond and Fischhoff (2017) find that "individuals with greater education, science education, and science literacy display more polarized beliefs" on issues correlated with political and religious identity. These issues include stem cell research, the Big Bang, human evolution, and climate change (Drummond and Fischoff 2017, 9587).…”
mentioning
confidence: 83%
“…Kahan et al (2012) show that polarization about climate change is greatest among individuals with the highest degrees of scientific literary and technical reasoning capacity. Drummond and Fischhoff (2017) find that "individuals with greater education, science education, and science literacy display more polarized beliefs" on issues correlated with political and religious identity. These issues include stem cell research, the Big Bang, human evolution, and climate change (Drummond and Fischoff 2017, 9587).…”
mentioning
confidence: 83%
“…Studies show that most individuals favor either scientific or religious ways of understanding (O'Brien & Noy, ) and that there is a possible negative correlation between levels of religiosity and performance in science and mathematics at the country level (Stoet & Geary, ). Though the relation between identity‐based polarization and education or scientific literacy can be very complex (Drummond & Fischoff, ), these studies point to the possibility that different forms of knowing can become mutually exclusive. This can become status threatening for climate change knowledge and is often discussed as undermining the case for climate change action.…”
Section: Are We Having a Status Problem?mentioning
confidence: 99%
“…National studies have found that religiosity corresponds to lower levels of scientific knowledge and negative attitudes toward science (McPhetres and Zuckerman ; Sherkat ; but see also Bhattacharjee ; Elsdon‐Baker ; and Roos ). Furthermore, Americans’ beliefs related to many science topics and socioscientific issues are polarized along religious and political lines (Drummond and Fischhoff ). At the same time, there is a trend for increasing association of particular religious or secular views with one or the other major political party, such as white evangelical Christians with the Republican party and seculars with the Democratic party (Wald and Calhoun‐Brown ).…”
Section: Contextmentioning
confidence: 99%